2019
DOI: 10.3126/ojn.v9i2.28413
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cranial Base Morphology of Pakistani Population in Skeletal Class I, II and III Malocclusions

Abstract: Introduction: Cranial Base integrate different patterns of growth in various regions of the skull such as the nasal cavity, the oral cavity, and the pharynx. Anteroposterior jaw position is thought to be affected by cranial base growth. Although scientific literature shows conflicting results regarding both positive and negative correlation between the cranial base and skeletal malocclusions. Materials & Method: 138 patients selected according to the Inclusion criteria were divided into three major c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…The present study results showed that there was no significant mean difference in saddle angle between three malocclusion classes which was in accordance to a study by Alia et al 9 The reason being anatomically temporomandibular joint placed away from mid sagittal plane so that changes in cranial base may not be translated to the mandible. Similarly, no correlation between sagittal skeletal relationship and cranial base angle could be identified in other studies.…”
Section: Discussionsupporting
confidence: 92%
“…The present study results showed that there was no significant mean difference in saddle angle between three malocclusion classes which was in accordance to a study by Alia et al 9 The reason being anatomically temporomandibular joint placed away from mid sagittal plane so that changes in cranial base may not be translated to the mandible. Similarly, no correlation between sagittal skeletal relationship and cranial base angle could be identified in other studies.…”
Section: Discussionsupporting
confidence: 92%